Conceptualizing the commercial determinants of dietary behaviors associated with obesity: A systematic review using principles from critical interpretative synthesis - Yanaina Chavez‐Ugalde; Russell Jago; Zoi Toumpakari; Matt Egan; Steven Cummins; Martin White; Paige Hulls; Frank De Vocht (Wiley, 2021)
Abstract Introduction Unhealthy diet is an important preventable risk factor for overweight and obesity. Identifying the key drivers of an unhealthy diet is an important public health aim. "Big Food" has been identified as an influential factor shaping dietary behavior and obesity, and their practices have broadly been labeled as the "commercial determinants of obesity," but there is a lack of definitions and conceptualizations for these terms. This review aimed to synthesize literature on the commercial determinants of dietary behavior associated with obesity. It presents the development of an integrative definition and a conceptual framework involving potential influences on dietary behavior, and it examines the prevalence of certain narratives within papers that focus on children and adolescents. Methods Four electronic databases (Ovid MEDLINE, PubMed, Web of Science, and Scopus) were searched up to December 2020. Eighty‐one articles met the inclusion criteria: they were published in a peer‐reviewed academic journal, described a practice from the food/beverage industry in relation to dietary behavior or obesity. Data were integrated using critical interpretative synthesis. Results The commercial determinants of dietary behavior are conceptualized in terms of three corporate spheres of action-political and legal; production, processing and design; and marketing and preference shaping-which enable powerful food industry to successfully pursue their business, market, and political objectives. The most frequently reported sphere of action targeting children and adolescents was marketing and preference shaping. Conclusions In the included literature, the commercial determinants of dietary behavior associated with obesity have been conceptualized as being part of a complex system where corporate practices are enabled by power structures. The proposed framework can facilitate a structured identification and systematic study of the impact of specific aspects of food industry's strategies and increase opportunities for primary prevention by anticipating industry responses and by discouraging corporate practices that harm health.